Legal Analysis of The Hijacking of The Maersk Alabama Ship by Somalian Robbers - Jonathan M D, Kenneth; Anindya, Vania; Alfiadi Farisqi, M Reval; Ul Hosna, Asmak (LifeSciFi, 2025)
The hijacking of the Maersk Alabama by Somali pirates in April 2009 attracted much attention worldwide and even revealed serious problems related to maritime security and the economic and political impacts in the region. The cargo ship sailing in Somali waters was hijacked by a group of pirates who intended to demand ransom. This case became the world's spotlight when Captain Richard Phillips was kidnapped, causing a crisis situation to develop, involving the United States military in his rescue efforts. This study aims to analyze the law of the hijacking of the Maersk Alabama ship by Somali robbers. This study uses a qualitative normative legal method with a conceptual and legislative approach. In this case study, an analysis was conducted of the factors that caused the piracy, including the political instability of Somalia, weak law enforcement in international waters, and poverty. Then, this study considers the international response to the threat of piracy and steps that can be taken to improve security in maritime areas, such as by conducting military patrols and cooperation between maritime countries. This case shows that ship hijacking can not only have an impact on the shipping sector but also has a broader connection to international relations and global trade. Therefore, an analytical or exploratory approach is needed that involves diplomatic, security, and economic efforts to address the problems in this case and the surrounding area.